Recombination statistics of non-equilibrium carriers in the model of a semiconductor with donor-acceptor pairs possessing variable recombination activity - Leyderman, A.Yu.; Uteniyazov, A.K.; Nsanbaev, M.T. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
The recombination rate of non-equilibrium carriers has been calculated for the model of the semiconductor with donor-acceptor pairs, the recombination activity of which decreases during excitation. It has been shown that, even at a very low inertia of intracomplex exchange, this process can lead to decreasing the recombination rate. The obtained results demonstrate a principal distinction from the classical Shockley–Read statistics. Швидкість рекомбінації нерівноважних носіїв була розрахована для моделі напівпровідника з донорно-акцепторними парами, активність рекомбінації яких знижується під час збудження. Було показано, що навіть при дуже низькій інерційності внутрішньокомплексного обміну цей процес може призвести до зниження швидкості рекомбінації. Отримані результати демонструють принципову відмінність від класичної статистики Шоклі–Ріда.